Title - Case of Unilateral Congenital Aural Atresia & Microtia with Cholesteatoma - Rahul, Kumar Singh; Amit, Goyal; Dramit, Kumar; Amber, Kesarwani; Gaurav, Kataria (Journal of Otolaryngology Advances, 2017)
We report a case of cholesteatoma associated with unilateral congenital aural atresia (CAA) and microtia, resulting in extracranial complication. A 13-year-old girl presented with right ear purulent discharge from pre and post auricular area with mastoid tenderness. On clinical examination, she had right grade II microtia with pre-auricular skin tag and healed scar tissue in periauricular region. On High Resolution Computerized Tomography (HRCT) scan of temporal bones, there was CAA of right ear with extensive cholesteatoma in middle ear cleft. The cholesteatoma was subsequently removed by radical mastoidectomy with uneventful post-operative period. Cholesteatoma associated with CAA may remain undiagnosed in early childhood resulting in life threatening temporal and intracranial complications.
Keywords: Congenital Aural Atresia; Microtia; Cholesteatoma; Unilateral; Radical Mastoidectomy